Riding on divergent but similar roads: Airbag or the Spanish experience of the American road movie - Induráin Eraso, Carmen (Estudios Ingleses de la Universidad Complutense, 2005)
The prolific number of road movies made in the 1990s in Spain constitutes a significant sign of the European importation of this genuinely American film genre. This paper explores the contribution of the road genre to the specific ways in which US culture permeates European culture, by examining what happens when such an American icon as the road is assimilated by Spanish contemporary cinema. In this paper I will concentrate on the popular Spanish road comedy, Airbag (Juan Manuel Bajo Ulloa, 1997) to examine how an American formula is “translated” into a Spanish context, becoming significant in Spanish culture. This paper will analyse the negotiation between what is specifically Spanish in the film, mainly its humour, within a Hollywood framework of male action on the road